2020
DOI: 10.18176/resp.00012
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of chronic hepatitis C treatment in the prison population in Spain

Abstract: Evaluar, en presos con hepatitis C crónica (HCc) pendientes de tratamiento, el coste-efectividad de tratarlos con antivirales de acción directa (AAD) frente a no tratarlos, y analizar el impacto clínico y económico del tratamiento sobre las complicaciones hepáticas y la mortalidad. Material y método: Se desarrolló un modelo de Markov para simular el tratamiento y proyectar la progresión de la enfermedad de una cohorte estimada de 4.408 reclusos con HCc tratados con AAD en dos años (el 50% cada año) frente a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The status quo was defined by limited access to HCV treatment. A separate study assessing treating prisoners in Spain by Marco et al also found DAA to be CE [12]. They found that comparing DAA treatment with no treatment was cost-effective (€690 per QALY).…”
Section: Cost-effectiveness Of Daas In Incarcerated Populationmentioning
confidence: 98%
See 1 more Smart Citation
“…The status quo was defined by limited access to HCV treatment. A separate study assessing treating prisoners in Spain by Marco et al also found DAA to be CE [12]. They found that comparing DAA treatment with no treatment was cost-effective (€690 per QALY).…”
Section: Cost-effectiveness Of Daas In Incarcerated Populationmentioning
confidence: 98%
“…Studies have consistently shown the use of DAAs against HCV to be cost-effective [10][11][12][13][14][15][16][17][18]. These studies differ in the country of origin, base populations, comparative treatment groups, and a variety of assumptions such as reinfection rates (See Table 1).…”
Section: Cost-effectiveness Of Daas In Pwidmentioning
confidence: 99%